Electromagnetic scattering laws in Weyl systems - Ming Zhou (Nature Portfolio, 2017)
Scattering characteristics are important optical properties but they depend strongly on the relative electromagnetic size and environment of a particle. Here, the authors study the frequency-dependence of the scattering cross section for a scatterer located inside a photonic Weyl system.